INFERENTIAL EVALUATION ON INSTRUCTOR AND RESOURCE PERSON COMPETENCIES OF EDUCATION AND TRAINING FOR SCHOOL SUPERVISOR IN INDONESIA - Yunus, Renny (International Journal of Psychosocial Rehabilitation, 2020)
Improvement of education quality is a joint responsibility that involves various groups including a training instructor. A training instructor must have subject expert and transfer txpert competencies. The expert transfer competency was still considered low so that the quality of human resources was also low. The purpose of this study was to evaluate the instructor and resource person of education and training on supervision (academic supervision and managerial supervision). This study used descriptive analysis method by combining field research and library research. The results of the study showed that instructors and implementations needed to be improved to achieve the desired work targets.